2019
DOI: 10.1111/jora.12517
|View full text |Cite
|
Sign up to set email alerts
|

Configurations of Autonomy and Relatedness in a Multiethnic U.S. Sample of Parent–Adolescent Dyads

Abstract: Configurations of autonomy and relatedness were explored in 232 adolescent–parent dyads. Youth (58% female) were 13–18 years old and ethnically diverse (38% Latino American, 32% European American, 30% African American). Cluster analysis was used to identify three distinct groups based on youth and parent reports of parental autonomy support and family relatedness. The three clusters differed on key demographics (e.g., parent education and income, immigrant background, ethnicity) and theoretically relevant indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
0
7
0
2
Order By: Relevance
“…In addition to the aspects reviewed and summarized above, some quantitative studies have used scales covering several smaller decisions (various matters) to measure children’s autonomy, independence, decision-making authority, and agency, such as staying out at night, friends, taking classes, dating, watching television, doing homework, doing household chores, going to bed, going back home after school and spending time outside school, spending money, clothes, hair, and makeup (Roche et al, 2015 ; Tran & Raffaelli, 2020 ; Varner & Mandara, 2014 ); or parent–child conflict frequency and intensity and children’s autonomy expectations for various everyday domains, such as chores, schoolwork, curfew, dating, family obligations, and going out (Bámaca-Colbert, Umaña-Taylor, & Gayles, 2012 , 2014 ; Eichelsheim et al, 2010 ; Estrada-Martínez et al, 2011 ; Fung et al, 2017 ; Juang, Syed, & Cookston, 2012 ; Roche et al, 2019 ; Titzmann, Gniewosz, & Michel, 2015 ). One quantitative study compared the independence in decision-making, representing whether adolescents were allowed to make their own decisions and rules about matters in daily life, between different generations of immigrants using a scale (Hamilton, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the aspects reviewed and summarized above, some quantitative studies have used scales covering several smaller decisions (various matters) to measure children’s autonomy, independence, decision-making authority, and agency, such as staying out at night, friends, taking classes, dating, watching television, doing homework, doing household chores, going to bed, going back home after school and spending time outside school, spending money, clothes, hair, and makeup (Roche et al, 2015 ; Tran & Raffaelli, 2020 ; Varner & Mandara, 2014 ); or parent–child conflict frequency and intensity and children’s autonomy expectations for various everyday domains, such as chores, schoolwork, curfew, dating, family obligations, and going out (Bámaca-Colbert, Umaña-Taylor, & Gayles, 2012 , 2014 ; Eichelsheim et al, 2010 ; Estrada-Martínez et al, 2011 ; Fung et al, 2017 ; Juang, Syed, & Cookston, 2012 ; Roche et al, 2019 ; Titzmann, Gniewosz, & Michel, 2015 ). One quantitative study compared the independence in decision-making, representing whether adolescents were allowed to make their own decisions and rules about matters in daily life, between different generations of immigrants using a scale (Hamilton, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…22 children interviewed in total 7–14 NA In-depth case studies and in-depth interviews Analysed thematically, using a technique advocated by Boyatzis (1998) Strong quality Stuart et al ( 2010 ) New Zealand International Journal of Intercultural Relations Qualitative A grounded theory approach, an exploratory study Immigrant children and parents 39 Parents and adolescents from Asian, Middle Eastern and African backgrounds: 32 participants (16 pairs) from family units with at least 1 parent and 1 child being interviewed; 5 adolescents and 2 parents took part without other family members 12–18 NA Interviews Content analysis guided by the principles of grounded theory, using NVivo database Strong quality Tanyas ( 2012 ) UK Journal of Youth Studies Qualitative A narrative-based qualitative method Immigrant children and parents 12 Young Turkish migrants 16–21 6, 50.0% Semi-structured interviews Narrative analysis Strong quality Titzmann et al ( 2015 ) Germany Journal of Youth and Adolescence Quantitative Cross-sectional Immigrant children and parents Mother–adolescent dyads: (1) 197 native German dyads and (2) 185 immigrant dyads from the former Soviet Union (1) M = 14.7, SD = 2.5 (2) M = 15.7, SD = 2.7 (1) NA, 53.0% (2) NA, 60.0% Questionnaires Descriptive analysis, intra-class correlation (one-way random), test mean-level differences, multivariate regression, regression analysis, using AMOS 20.0 Strong quality Tran and Raffaelli ( 2020 ...…”
Section: Appendixmentioning
confidence: 99%
“…Today, adolescents have been required to have an autonomous-related self with behavioral autonomy but emotional relatedness with their family. (Tran & Raffaelli, 2019). In this family model, parental control that provides explanation and reasoning is valued by allowing adolescents to develop autonomy because there is no dominant tendency to demand blind obedience (Kag ˘ıtc ¸ıbas ¸ı, 2013).…”
Section: Parent-child Interactions and Relationship In The View Of Childrenmentioning
confidence: 99%
“…When parents in this study allowed their children to develop autonomy but still supported them emotionally and financially, their children developed confidence in themselves and optimistic views toward the world with clearer goals. Tran and Raffaelli (2019) showed the relation between adolescents' awareness of autonomy support and the closeness to their parents. In this study, adolescents who ranked high in feeling they have autonomy to control their own life rather than be swayed by their parents or other forces indicated that they admire their parents' lives and recognize the secure base their parents provide.…”
Section: Adolescents' Need For Autonomy and Well-being In Relation To Parental Supportmentioning
confidence: 99%
See 1 more Smart Citation